Stability of primary emulsion assisted with nanoparticle in emulsion liquid membrane process for zinc extraction - Sufi Suliman, S. (Elsevier Ltd, 2022)
In the present work, primary water-in-oil (W/O) emulsion consisting blended surfactant and nanoparticle is used for the improvement of ELM stability for zinc extraction. The components used in ELM were di-(2-ethylhexyl)phosphoric acid (D2EHPA) and bis(2,4,4-trimethylpentyl)thiophosphinic acid (Cyanex 302) as a base and synergistic carrier, palm oil as a diluent, sorbitan monooleate (Span 80) and polyoxyethylene sorbitan monooleate (Tween 80) as a surfactant, iron (III) oxide (Fe2O3) as a nanoparticle stabilizer and acidic thiourea as a stripping agent. There are several operating parameters including hydrophilic-lipophilic (HLB) value, mixed surfactant concentration, homogenizer speed as well as nanoparticle concentration were investigated in primary W/O emulsion preparation. The results show that emulsion stability increases up to 88 while droplet diameter decreases by 70 at HLB 8, 5 (w/v) of blended mixture surfactant, 8000 rpm of homogenizer speed and 0.02 (w/v) of nanoparticle concentration at fixed 3 min of emulsification time within 60 min of phase separation. It is expected that the extraction of zinc during the formation of W/O/W emulsion increases as it may offer large surface area for solute pertraction and reduced destabilization phenomenon. Hence, the usage of blended mixture surfactant accompanied by nanoparticle (Fe2O3) in the emulsion making has high potential to enhance the emulsion stability in emulsion liquid membrane process of zinc extraction. Â© 2022